WHAT IS THE TITLE OF MERREW? - Islam I. AMER (Fayoum University, 2017)
The title was found on some vessels recovered from the pyramid of Djoser, followed byMrrw(Merrew) the name of an unknown employee. This title is one of the mysterious and unclear titles. Researchers have offered various readings of this title (rmnzx?;zx a(w)?;zxXrt-a?), thus giving different meanings. The paper aims at identifying this employee through determining the most correct and closest reading of this title, deciding the time of its emergence, defining its meaning.